Effectiveness of low-cut modified amplification strategy and channel-free hearing aid in individuals with auditory neuropathy spectrum disorder. - Prabhu, Prashanth; Barman, Animesh (International Journal of Audiology, 2017)
Objective: The present study attempted to compare the aided benefit using low-cut modified amplification and channel-free hearing aids in individuals with auditory neuropathy spectrum disorder (ANSD). It was also attempted to determine these effects in good and poor performers with ANSD. Design: Cross-sectional within group pretest, post-test design. Study sample: Twenty-five individuals with acquired ANSD were selected for the study. The study sample included 11 males and 14 females between the age ranges of 17-40 years (mean age of 24.6 years). Results: The results of the repeated measures analysis of variance (ANOVA) showed that aided benefit was significantly higher with the channel-free hearing aid. Mixed ANOVA results showed that the improvement was more in good performers than poor performers with ANSD. Multiple regression analyses showed that speech identification scores are a strong predictor of aided benefit. Conclusions: The results of the present study suggest that channel-free hearing aids and low-cut modified amplification can be used as an efficient alternative technique during hearing aid fitting for individuals with ANSD. However, further evidence-based studies on a larger group are essential to validate the results.